2020
DOI: 10.1002/tesq.592
|View full text |Cite
|
Sign up to set email alerts
|

Obscuring Equity in Dual Language Bilingual Education: A Longitudinal Study of Emergent Bilingual Achievement, Course Placements, and Grades

Abstract: Dual language bilingual education (DLBE) is a unique form of bilingual education that has the potential to preserve and develop the heritage languages of emergent bilinguals, foster high levels of bilingualism, and address academic disparities, thereby changing emergent bilinguals’ educational conditions and learning outcomes. Yet, DLBE schools and programs are nested within a broader sociopolitical context which may attenuate the benefits of DLBE. To address the construction of DLBE as a panacea for equity, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Unlike the students in the Driscoll case, las escuelitas participants sometimes graduated high school a year early because they had been placed in 1-A, as they knew how to read, hold a pencil, and write their palitos and bolas. Tracking English learners into remedial courses carries on today, even when said students are enrolled in purportedly more rigorous dual language programs (Morita-Mullaney et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the students in the Driscoll case, las escuelitas participants sometimes graduated high school a year early because they had been placed in 1-A, as they knew how to read, hold a pencil, and write their palitos and bolas. Tracking English learners into remedial courses carries on today, even when said students are enrolled in purportedly more rigorous dual language programs (Morita-Mullaney et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have found that TWI programs improve academic achievement for both ELs and native English speakers (Collier & Thomas, 2004; Rolstad et al, 2005; Steele et al, 2017; Umansky & Reardon, 2014; Valentino & Reardon, 2015). ELs perform better on standardized tests in mathematics and English language arts than their peers in English as a second language classes and tend to have higher grades and higher likelihood of taking advanced courses in middle school after participating in an elementary TWI program (Morita-Mullaney et al, 2020). TWI positively impacts not only language development but also academic outcomes in other subject areas (Steele et al, 2017; Umansky & Reardon, 2014; Valentino & Reardon, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estrada (2014) examined ELL course placement policies in four California middle schools and found that ELLs' class schedules mostly consisted of few or no core contents classes, remedial and English language support classes, both of which did not serve academic purpose. Even high-achieving ELLs could not as fully access to academic subjects as their non-ELLs did (Estrada, 2014;Morita-Mullaney et al, 2020). Gándara and her colleagues (2003) who examined transcripts of high school students from two California school districts also found the similar course placement patterns; ELLs' class schedules showed multiple empty class periods, remedial classes, too many electives while having few or no core contents areas, especially science.…”
Section: Coursesmentioning
confidence: 99%
“…Thus, their findings suggest that ELLs are consistently denied access to advanced core courses even though they share the similar observed characteristics and achievement level with non-ELLs. Qualitative studies have also documented ELLs' limited access to advanced courses or core-contents area classes (Estrada, 2014;Gándara, Rumberger, Maxwell-Jolly, & Callahan, 2003;Morita-Mullaney, Renn, & Chiu, 2020;Thompson, 2017;Xiong, 2010) despite their high prior achievement (Kanno, 2018;Zuniga et al, 2005) or high aspiration for post-secondary education (Kanno & Kangas, 2014).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation